2015
DOI: 10.1007/s12253-015-9957-0
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Predictors of Bone Metastases in Breast Cancer Patients

Abstract: Bones are the most common metastatic site of relapse in breast cancer patients and the prediction of bone metastases (BM) risk might prompt developing preventive and therapeutic strategies. The aim of the study was to correlate imumohistochemical (IHC) expression of selected proteins in primary breast cancer with the occurrence of BM. We analyzed expression of proteins potentially associated with BM in primary tumors of 184 patients with metastatic breast cancer (113 with- and 71 without BM). Expression of est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Breast cancer commonly metastasize to the bone and the hormonal receptor status can predict the metastatic site (3). Most of the patients in the study was in between 50-60 years and least patient was in age between 30-40 years and 70-80 years which was consistent with study conducted by Neesa et al (2018).…”
Section: Discussionsupporting
confidence: 89%
“…Breast cancer commonly metastasize to the bone and the hormonal receptor status can predict the metastatic site (3). Most of the patients in the study was in between 50-60 years and least patient was in age between 30-40 years and 70-80 years which was consistent with study conducted by Neesa et al (2018).…”
Section: Discussionsupporting
confidence: 89%
“…A more recent study aimed to relate the immunohistochemical expression of specific proteins in primary tumours with the development of BM [ 86 ]. For this purpose a total of 184 patients were analysed (n = 113 with BM and n = 71 with extraskeletal metastases) for ER, PR, HER2, Ki67, and six exploratory proteins: COX2, CK5/6, CXCR4, PTHR1, OPN, and CaSR.…”
Section: Risk Factors For Bone Metastasesmentioning
confidence: 99%
“…PTHR1 overexpression was found in 34% of patients with BM compared to 16% without BM (p = 0.007). While there seemed to be a positive relationship between PTHR1 overexpression and BM in the univariate analysis, this did not hold true in the multivariate model where only ER and absence of cytoplasmic OPN were independent risk factors for BM (p = 0.002 and p = 0.018) [ 86 ].…”
Section: Risk Factors For Bone Metastasesmentioning
confidence: 99%
“…Alongside this molecular knowledge, multiple bone metastasis-specific biomarkers have been proposed. For example, Winczura et al ( 2015 ) have found that a reduction of osteopontin was consistently observed in patients who developed bone metastasis, whereas Mihai et al ( 2006 ) have found that the calcium-sensing receptor (CaR) was commonly expressed in breast tumours, which metastasised to the bone. Although our models uncovered some proteins previously known to be associated with metastasis, it also uncovered several proteins that generally have not been studied in the context of BC tropism to specific metastatic sites/tissues, or have not been implicated directly in regulating metastasis.…”
Section: Discussionmentioning
confidence: 99%